Effect of offshore waves and vegetation on the sediment budget in the Virginia Coast Reserve (VA). Issue 12 (28th July 2020) - Nardin, William; Lera, Sara; Nienhuis, Jaap
Abstract: The potential for rapid coastline modification in the face of sea‐level rise or other stressors is alarming, since coasts are often densely populated and support valuable infrastructure. In addition to coastal submergence, nutrient‐related water pollution is a growing concern for coastal wetlands. Previous studies found that the Suspended Sediment Concentration (SSC) of coastal wetlands acts as a first‐order control of their sustainability, but SSC dynamics are poorly understood. Our study focuses on the Virginia Coast Reserve (VCR) Long Term Ecological Research (LTER) site, a shallow multiple tidal inlet system in the USA. We apply numerical modelling (Delft3D‐SWAN) and subsequent analyses to determine SSC dynamics within the VCR. In particular, we consider two important controls on SSC in the system: vegetation (seagrass and salt marsh) and offshore waves. Our results show that vegetation colonies and increased wave energy lengthen water residence time. The reduction in the tidal prism decreases SSC export from the bay via tidal inlets, leading to increased sediment retention in the bay. We found that alongshore currents can enhance lagoon SSC by importing fine sediments from an adjacent inlet along the coastline. Our numerical experiments on vegetation seasonality can improve the understanding of wave climate impact on coastal bay sediment budget. Offshore waves increase sediment export from coastal bays, particularly during winter seasons with low vegetation density. Therefore, our study can help managers and stakeholders to understand how to implement restoration strategies for the VCR. © 2020 John Wiley & Sons, Ltd. Abstract : The proposed study focuses on the Virginia Coast Reserve (VCR), a shallow multiple tidal inlet system in the USA. We apply numerical modelling and we consider two important controls on Suspended Sediment Concentration (SSC) in the system: vegetation (seagrass and salt marsh) and offshore waves. Our results show that vegetation colonies and increased wave energy lengthen water residence time. The reduction in the tidal prism decreases SSC export from the bay via tidal inlets, leading to increased sediment retention in the bay. We found that alongshore currents can enhance lagoon SSC by importing fine sediments from an adjacent inlet along the coastline.